Mac OS X Leopard phrasebook : essential code and commands - Tiemann, Brian (Developer's library., 2008)
"Mac OS X Leopard Phrasebook gives you the complete command phrases you need to take full advantage of Leopard's hidden and undocumented power underneath the graphical user interface: time-saving solutions for effectively working with flies, folders, the Finder, Spotlight, text files, servers, disks, CDs/DVDs, permissions, printing, applications, Expose, networking, security, and much more."--Jacket